1998
DOI: 10.1097/00007890-199807270-00004
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Specific Portal Blood Transfusion in Intestinal Transplantation

Abstract: Portal DST at the time of total bowel transplantation and posttransplant immunosuppression with tacrolimus prevent rejection and significantly increase graft survival. The combination of portal antigen presentation and tacrolimus needs to be studied in clinical bowel transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Several previous studies have shown prolonged intestinal allograft survivals to 100–200 days in dogs and pigs under CYS, prednisone, or FK506 regimens (12–18). In those studies, the majority of recipients sustained rejection, malnutrition, and infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown prolonged intestinal allograft survivals to 100–200 days in dogs and pigs under CYS, prednisone, or FK506 regimens (12–18). In those studies, the majority of recipients sustained rejection, malnutrition, and infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our current findings, in a later study from the same center that analyzed recipients on tacrolimus, no immunologic impact of portal venous drainage was observed (43). Similarly, in an experimental porcine intestinal transplant study on the effect of tacrolimus vs. cyclosporine A immunosuppression, and of portal vs. systemic antigen infusion in portally drained small intestinal grafts, the type of immunosuppressive agent was more significant than the route of perioperative antigen administration (15). Thus, our results analyzed in conjunction with historical and experimental observations suggest that, while portal venous drainage may confer a modest immunologic benefit, any such benefit is relatively insignificant when compared with the combined effect of more powerful immunosuppression and increasing center experience: according to our multivariate analysis, even for recipients on tacrolimus, outcomes were better in the current than in the previous era.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies have demonstrated that antigen presented to the liver via the portal vein can result in the induction of antigen‐specific systemic hyporesponsiveness (1–14). The distinct mechanisms leading to such a functionally tolerant state are not completely understood, but require the processing of antigen by hepatic macrophages (15–18).…”
Section: Introductionmentioning
confidence: 99%
“…But this therapy led to a higher risk of death from the development of severe infections, which stemmed from the side effects of immunosuppression. 56 Murase et al eliminated mature lymphoid elements from the bowel allografts using ex vivo irradiation; as a result, chronic rejection was prevented with adjunct donor BMC infusion without causing GVHD. 57 For decreasing the morbidity and mortality associated with the use of lethal conditioning regimens in a rat small bowel transplant model, low doses of TBI with ATS serum were also used.…”
Section: Intestine Transplantationmentioning
confidence: 99%